An evolution of the acceptance tests of water-tube boilers - Rataj , Zbigniew (Instal, 2020)
The article reviews the acceptance standards for water-tube boilers. National standard PN-72/M-34128, standard DIN 1942 Acceptance Test Code for Steam Generators, European Standard PN-EN 12952-15 Water-tube boilers and auxiliary installations – Part 15: Acceptance tests, as well as ASME PTC-4 Fired Steam Generators. Performance Tests Codes have been discussed. Evolutionary changes introduced in individual standards, related to the development of boiler structures and auxiliary installations are shown. A classic definition of boiler efficiency is provided (direct and indirect method). Attention is paid to the essence of the correct definition of boiler efficiency, as efficiency is an important operating parameter and is used to assess boiler performance and assess compliance of parameters and guaranteed parameters in acceptance tests. The attention was turned onto possible errors, which might occur when estimating the mean year boiler efficiency.